RANCANG BANGUN SISTEM AKUISISI DATA KELEMBABAN DAN PENGENDALIAN SUHU PADA BOX SARANG NYAMUK MENGGUNAKAN PENGENDALI TIPE PID BERBASIS MIKROKONTROLER ATMEGA8535 UNTUK PENGAMATAN SIKLUS HIDUP NYAMUK Aedes aegypti - Ibnu Sulistiyono; Ainie Khuriati RS (Youngster Physics Journal, 2012)
Abstract In this research, the PID controller (Proportional Integral Derivative) temperature control work in mosquito nest box automatically to observate life cycle of insects especially the Aedes aegypti species. This is an effort in research to looking for alternative solutions in the prevention of the disease dengue fever. Temperature and humidity SHT11 censor is used as an indicator to manage the light sandwiches intencity useful as actuators. This PID method is applicated on the microcontroller ATMEGA8535 by LCD as viewer of the results and use the computer to monitore the humadity and controls the temperatures of the insect cage settpoint box by value in the input to the processor unit (PC). The PID parameters are determined by use tunning by Ziegler Nichols reaction curve method to get the best parameter value . From the test result we get the controlling parameter  of the PID control are Kp = 51,09; Ki = 77,41; dan Kd = 8,42. Key words : PID, SHT11, Mikrokontroler Atmega8535, LCD, PC, Ziegler Nichols.